2018
DOI: 10.1371/journal.pone.0190419
|View full text |Cite
|
Sign up to set email alerts
|

Early neonatal mortality and neurological outcomes of neonatal resuscitation in a resource-limited setting on the Thailand-Myanmar border: A descriptive study

Abstract: BackgroundOf the 4 million neonatal deaths worldwide yearly, 98% occur in low and middle-income countries. Effective resuscitation reduces mortality and morbidity but long-term outcomes in resource-limited settings are poorly described. This study reports on newborn neurological outcomes following resuscitation at birth in a resource-limited setting where intensive newborn care including intubation is unavailable.MethodsRetrospective analysis of births records from 2008 to 2015 at Shoklo Malaria Research Unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…intubation, incubators, surfactant, parenteral nutrition etc. is available 25 . Women who need caesarean section or who have complex medical conditions are transferred by car to Thai hospitals (45 to 90 minutes away).…”
Section: Methodsmentioning
confidence: 99%
“…intubation, incubators, surfactant, parenteral nutrition etc. is available 25 . Women who need caesarean section or who have complex medical conditions are transferred by car to Thai hospitals (45 to 90 minutes away).…”
Section: Methodsmentioning
confidence: 99%
“…Globally, four million neonatal deaths are registered annually, representing nearly half of under-five child mortality [ 1 ]. 73 % of neonatal deaths occur in the first week of life, especially during the first 24 hours after delivery [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, four million neonatal deaths are registered annually, representing nearly half of under-five child mortality [ 1 ]. 73 % of neonatal deaths occur in the first week of life, especially during the first 24 hours after delivery [ 1 ]. 98 % of all neonatal deaths occur in low- and middle-income countries (LMICs), and 77 % of those in Asia and Sub-Saharan Africa [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study indicated that basic resuscitation at birth prevents abnormal neurodevelopmental outcomes at one year of age when compared to low-risk newborns [9]. Other factors, like late-preterm birth (34 to 36 weeks) have also been found to lead to long-term cognitive issues [10,11].…”
mentioning
confidence: 99%